Examining Franz Brentano's Concepts of Good and Bad in Sophocles' Antigone: Insights for Islamic Moral Consideration - Bita Iraji (Indonesian Journal of Islamic Literature and Muslim Society, 2024)
The purpose of this research is to investigate the good and bad themes of love and recognition in Sophocles' Antigone, which is within the framework of Franz Brentano's philosophical concepts and Islamic views. The main questions asked are: How do love and recognition help to understand good and bad actions in the narrative of "Antigone"? And how do these themes resonate in Islamic moral views? To answer these questions, the research uses the method of literary analysis based on historical texts, philosophical theories, and religious insights. The analysis shows that the character of Antigone shows the conflict between family loyalty and social rules, showing that love can lead to noble actions with tragic consequences. Meanwhile, Creon's character represents the dangers of pride and blind judgment and tries to enforce human laws over divine principles. The findings highlight the complexity of ethical decisions and show that what is considered good or bad may vary based on individual perspectives and social norms. Finally, this research shows how Antigone's narrative reflects the interplay of love, cognition, and ethical dilemmas and makes Brentano's thoughts on ethics reconsidered in the light of Islamic teachings. This study concludes that a deep commitment to these themes encourages a more nuanced understanding of moral ambiguity and human behavior.